Conceptual Model Improving Secure Data Handling Within Confectionery Enterprise Systems - Ugwu-Oju Ukamaka Mary,; Nwankwo Constance Obiuto,; Okeke Obinna ThankGod, (International Journal of Scientific Research in Science and Technology, 2024)
Secure data handling has become a foundational requirement in modern confectionery enterprise systems as manufacturers increasingly depend on interconnected digital platforms for recipe formulation, production control, supply-chain coordination, and quality assurance. The unique characteristics of confectionery operations such as proprietary ingredient compositions, precise thermal and mixing parameters, allergen-control data, and batch-level traceability demand advanced mechanisms that protect information integrity, confidentiality, and availability. This abstract presents a conceptual model designed to enhance secure data handling across confectionery enterprises by integrating technological, procedural, and governance-based controls. The model emphasizes the unification of data protection practices across both operational technology (OT) and information technology (IT) layers, ensuring seamless security for process data, enterprise resource planning (ERP) records, and digital production logs. Core components include encrypted data pipelines for transferring formulation data and production parameters, role-based access control mechanisms for managing user privileges, and blockchain-enabled traceability for safeguarding critical batch information and audit trails. The conceptual model also incorporates real-time anomaly detection systems and integrity-verification algorithms to prevent unauthorized data manipulation affecting quality, safety, or regulatory compliance. Furthermore, the model embeds governance frameworks aligned with ISO 27001, NIST Cybersecurity Framework, and food industry-specific digital safety standards to ensure structured oversight and consistent enforcement. Workforce capability development is integrated as a foundational element, acknowledging the importance of cybersecurity awareness, data-handling hygiene, and safe interactions with digital manufacturing systems. The approach enables confectionery enterprises to mitigate data breaches, maintain reliable production records, protect intellectual property, and strengthen supply-chain trust. Overall, the conceptual model offers a holistic framework that enhances secure data handling, supports digital transformation, and reinforces operational resilience across confectionery manufacturing environments. By combining technical safeguards, governance structures, and human competencies, the model provides a scalable and adaptive foundation for future-ready data protection in a highly digitized confectionery sector.
Keywords: secure data handling; confectionery enterprise systems; data integrity; encryption; traceability; OT/IT integration; blockchain; cybersecurity; digital governance; data protection